Suppose $$\frac{{{{\sin }^4}(\alpha )}}{a} + \frac{{{{\cos }^4}(\alpha )}}{b} = \frac{1}{{a + b}}$$ for some $a,b\ne 0$.

Why does $$\frac{{{{\sin }^8}(\alpha )}}{{{a^3}}} + \frac{{{{\cos }^8}(\alpha )}}{{{b^3}}} = \frac{1}{{{{(a + b)}^3}}}$$

  • 1
    $\begingroup$ Very curious identity. I'd wager it's related to ellipses somehow. Where did you encounter it? Is it an assignment? $\endgroup$ – Yuriy S Nov 11 '16 at 11:15
  • 4
    $\begingroup$ @YuriyS Just apply Cauchy-Schwarz and observe that the equality holds. The conclusion easily follows. $\endgroup$ – Cave Johnson Nov 11 '16 at 11:19
  • 1
    $\begingroup$ More specifically, you can use Titu's version of the Cauchy Schwarz here, which directly gives the equality condition. $\endgroup$ – Sawarnik Nov 16 '16 at 17:40

There is a very direct way to solve this. First, use the given equation to find, for example, $\sin^2 \alpha$:

$$x=\sin^2 \alpha$$

$$\frac{1}{a} x^2+\frac{1}{b}(1-x)^2=\frac{1}{a+b}$$

Solving this easy quadratic, we get a single root:

$$x=\frac{a}{a+b}=\sin^2 \alpha$$

It follows:

$$1-x=\frac{b}{a+b}=\cos^2 \alpha$$

Now substitute these values into the second equation and see that it holds.

  • $\begingroup$ this question from the book ' бескин trygonometry' but your solution is better then his :) $\endgroup$ – yavuz Feb 22 '18 at 10:31

Solving the system $$\begin{cases}X^2+Y^2=1\\\dfrac{X^4}{a}+\dfrac{Y^4}{b}=\dfrac{1}{a+b}\end{cases}$$ where obviously $X$ and $Y$ are the sinus and cosinus respectively, one has $$X=-\sqrt{\dfrac{a}{a+b}}\\Y=\pm\sqrt{\dfrac{b}{a+b}}$$

This gives directly the equalities $\dfrac{X^8}{a^3}=\dfrac{a^4}{a^3(a+b)^4}$ and $\dfrac{Y^8}{b^3}=\dfrac{b^4}{b^3(a+b)^4}$ hence the result



The general expression is:$$\frac{\sin^{4n}\theta}{a^{2n-1}} + \frac{\cos^{4n}\theta}{b^{2n-1}} = \frac{1}{(a+b)^{2n-1}}~, ~~n\in \mathbb N$$

From the given relation, it can be written \begin{align}(a+b)\left(\frac{\sin^4\theta}{a}+ \frac{\cos^4\theta}{b}\right) &= \left(\sin^2\theta + \cos^2\theta\right)^2\\ \implies\sin^4\theta + \cos^4\theta + \frac ba\sin^4\theta + \frac ab\cos^4\theta &= \sin^4\theta + 2\sin^2\theta\cos^2\theta + \cos^4\theta\\ \implies~~~~~~~~~~~ \left(\sqrt{\frac ba}\sin^2\theta - \sqrt\frac ab\cos^2\theta \right)^2&= 0\\ \implies~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ \frac{\sin^2\theta}{a}&= \frac{\cos^2\theta }{b}\\ \implies~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ \frac{\sin^2\theta}{a}= \frac{\cos^2\theta }{b} &= \frac{\sin^2\theta + \cos^2\theta}{a+b}\end{align}

From this, it can be concluded that $$\sin^2 \theta = \frac a{a+b};~~~\cos^2\theta = \frac{b}{a+b} \,.$$

It's a matter of substituting the values to prove the general and the desired expression.

  • 1
    $\begingroup$ You should provide a reference for your inital statement. Otherwise you're just begging the question. $\endgroup$ – Carl Witthoft Nov 11 '16 at 19:57
  • 1
    $\begingroup$ @CarlWitthoft, This can be proved by mathematical induction as well as substituting the values we got from the given expression; I think OP can prove it. $\endgroup$ – user142971 Nov 12 '16 at 2:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.